Daily Reports of Positive and Negative Affect and Alcohol and Marijuana Use Among College Student and Nonstudent Young Adults. (2nd January 2016) - Patrick, Megan E.; Yeomans-Maldonado, Gloria; Griffin, Jamie
ABSTRACT: Background : Daily affect and substance use covary among college students, but little is known about these associations among young adults not in college. Objectives : The current pilot study examines associations between positive and negative affect and alcohol and marijuana use, with a focus on differences between college student and nonstudent young adults. Methods : High school seniors completed a baseline survey during the spring of 2012 and were then randomly selected to participate in an intensive measurement follow-up. Participants in the follow-up ( N = 72, 40.3% men, 77.8% White, 66.7% full-time college students) completed up to 14 consecutive web-based daily surveys during the fall after high school completion. Multilevel models in which days (Level 1) were nested in persons (Level 2) were estimated. Results : Weekend days were associated with increased alcohol use among all young adults, increased marijuana use among college students, and decreased marijuana use among nonstudents. For young adults not in college, greater daily positive affect was associated with increased likelihood of binge drinking, consuming a greater number of drinks, and lower odds of marijuana use; greater daily negative affect was associated with lower odds of alcohol use and lower odds of binge drinking for non-students. For college students, greater daily negative affect was associated with lower odds of marijuana use. Conclusions/Importance : Daily affect and alcohol and marijuana use covary among young adults, though these associations differ between students and non-students. Results highlight the need to examine predictors of alcohol and marijuana use among young adults who do not attend college.